First evidences of Acartia bifilosa resting eggs in sediments of the Urdaibai estuary (Bay of Biscay): abundance and hatching success. - Uriarte, I. & F. Villate (Scientia Marina, 2006)
The abundance and hatching success of Acartia bifilosa resting eggs in subtidal sediments of the Urdaibai estuary was analysed in the context of a study on the spatial and temporal dynamics of this species. Two sediment cores of 20 to 30 cm depth were obtained at two sites of the middle zone, where the accumulation of mud and organic particles is favoured. Laboratory incubations were performed to determine the hatching success of eggs and identify newborns. Resting egg abundance was around 10 7 eggs m-2 , and was higher at the site where the A. bifilosa population maintains an optimal position in the water column. The lower egg abundance in upper layers, as corresponds to winter, was associated with the seasonal dynamics of planktonic populations. On average, the hatching success was >50% at both sites. The lack of significant differences in the hatching success according to sediment depth suggests that eggs remain viable after being buried for a long-time in anoxic conditions. This enables us to infer that the benthic egg bank of A. bifilosa in this estuary is a safe source of recruits into the planktonic population, and plays a crucial role in recuperation and maintenance of the population.